2020
DOI: 10.1186/s13068-020-01778-w
|View full text |Cite
|
Sign up to set email alerts
|

Modification of transcriptional factor ACE3 enhances protein production in Trichoderma reesei in the absence of cellulase gene inducer

Abstract: Background: Trichoderma reesei is one of the best-known cellulolytic organisms, producing large quantities of a complete set of extracellular cellulases and hemicellulases for the degradation of lignocellulosic substances. Hence, T. reesei is a biotechnically important host and it is used commercially in enzyme production, of both native and foreign origin. Many strategies for producing enzymes in T. reesei rely on the cbh1 and other cellulase gene promoters for high-level expression and these promoters requir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…A previous report suggested that removing the C-terminal segment of the ACE3 regulator increased cellulase production in T. reesei ( 53 ). Comparative analysis of NcCLR-2 and MtCLR-2 revealed an extra segment in the C terminus of MtCLR-2 compared with its ortholog in N. crassa after 722 aa.…”
Section: Resultsmentioning
confidence: 98%
“…A previous report suggested that removing the C-terminal segment of the ACE3 regulator increased cellulase production in T. reesei ( 53 ). Comparative analysis of NcCLR-2 and MtCLR-2 revealed an extra segment in the C terminus of MtCLR-2 compared with its ortholog in N. crassa after 722 aa.…”
Section: Resultsmentioning
confidence: 98%
“…In T. reesei , for example, the transcription factor CRE1 is the main repressor of lignocellulolytic enzyme expression, while XYR1 is its main transcriptional activator. Mutations that caused the first silencing and the second’s overexpression demonstrated elevated levels of extracellular cellulase secretion, producing hypersecretory T. reesei strains [ 359 , 360 ]. The combinatorial engineering of three transcriptional activators in P. oxalicum (ClrB, XlnR, and AraR) also demonstrated the generation of a strain with an increase in lignocellulolytic enzymes production from 3.1 to 51.0-fold, in addition to a more significant release of fermentable sugars from corn fiber, when compared with the original strain enzymes [ 361 ].…”
Section: Recent Advancesmentioning
confidence: 99%
“…This finding was further corroborated by a recent study in which different variants of Ace3, having a common Zn2Cys6 domain in the N-terminal and different truncations in the C-terminal region were expressed in T. reesei . It was observed that a truncation of 7–17 amino acids in the C-terminal region led to a 1.5–twofold increase in total cellulase production in presence of glucose, and a threefold increase in activity in presence of lactose, whereas a longer truncation of 20–25 amino acids led to severe reduction in protein production [ 63 ]. The authors have suggested two possibilities for this interesting observation—either the presence of an inhibitory domain in this region or the occurrence of a stretch of hydrophobic residues, which could interact with other transcription factors leading to reduced expression [ 63 ].…”
Section: Transcriptional Regulators Involved In the Regulation Of Cel...mentioning
confidence: 99%